Exploring genetic diversity of tomato (Solanum lycopersicum L.) germplasm of genebank collection employing SSR and SCAR markers - Evangelos D. Gonias (2019)
© 2019, Springer Nature B.V. Α wide selection of tomato (Solanum lycopersicum L.) genotypes with diverse origin and breeding history (14 modern varieties, 71 landraces and 22 commercial hybrids) has been initially genotyped with a selection of highly informative simple sequence repeat (SSR) markers and two SCAR markers originally developed for resistance against two main fungal tomato diseases. Our data revealed a high level of genetic diversity across the selection, with an average number of alleles per locus (NA) equal to 9.6, and the average polymorphism information content (PIC) equal to 0.74. Further, the selected SSRs have been verified as highly polymorphic and able to discriminate different patterns within our collection, amplifying a total of 56 alleles. Cluster analysis indicated that the collection could be grouped into three clades, with most of landraces and modern varieties being clearly distinguished from hybrids, but also with each other. Breeding involve the selection of specific phenotypes, limiting the genetic variation of the population. Herein, a notable genetic loss due to breeding was detected in the modern tomato gene pool.